2012
DOI: 10.1155/2012/893048
|View full text |Cite
|
Sign up to set email alerts
|

BRASERO: A Resource for Benchmarking RNA Secondary Structure Comparison Algorithms

Abstract: The pairwise comparison of RNA secondary structures is a fundamental problem, with direct application in mining databases for annotating putative noncoding RNA candidates in newly sequenced genomes. An increasing number of software tools are available for comparing RNA secondary structures, based on different models (such as ordered trees or forests, arc annotated sequences, and multilevel trees) and computational principles (edit distance, alignment). We describe here the website BRASERO that offers tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…For the structure-comparative benchmarks, we took four different data sets from the Brasero (Allali et al 2012) collection, namely Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by rnajournal.cshlp.org Downloaded from SRP, sRNA, miRNA, and tRNA. Each data set consists of three parts: The first one is a small number of RNAs together with their known structures R of the given RNA family F; the second is a set of RNA secondary structures T2 folded from a set of RNA sequences that belong to F using mfold (Zuker and Stiegler 1981) or RNAshapes; and the third, called noise, is a set of RNA secondary structures F2 folded from a set of RNA sequences that are either random segments from viral genomes or from encode sequences.…”
Section: Data Set and Benchmark Procedures For Structure Comparisonmentioning
confidence: 99%
“…For the structure-comparative benchmarks, we took four different data sets from the Brasero (Allali et al 2012) collection, namely Cold Spring Harbor Laboratory Press on May 10, 2018 -Published by rnajournal.cshlp.org Downloaded from SRP, sRNA, miRNA, and tRNA. Each data set consists of three parts: The first one is a small number of RNAs together with their known structures R of the given RNA family F; the second is a set of RNA secondary structures T2 folded from a set of RNA sequences that belong to F using mfold (Zuker and Stiegler 1981) or RNAshapes; and the third, called noise, is a set of RNA secondary structures F2 folded from a set of RNA sequences that are either random segments from viral genomes or from encode sequences.…”
Section: Data Set and Benchmark Procedures For Structure Comparisonmentioning
confidence: 99%
“…The eye was long regarded an immune privileged organ, but emerging evidence has shown that the systemic immune system indeed has a crucial role in the pathophysiology of AMD 8 10 . In AMD, peripheral inflammatory/classical monocytes are recruited to the sites of retinal injury where they differentiate into macrophages 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness describes properties of the arterial vascular system such as distensibility, compliance, and elastic modulus [5]. It can be assessed at different sites, such as systemically (pulse wave analysis), regionally (PWV), or locally (relating a change in the area of an artery to distending pressure) [6].…”
Section: Introductionmentioning
confidence: 99%